EKSPERIMENTASI MODEL KOOPERATIF TIPE TEAMS GAME TOURNANENT TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI KEMAMPUAN AWAL SISWA KELAS IX SMPN 28 SAROLANGUN - Susi Susanti (Pendidikan Matematika | STKIP YM Bangko, 2020)
Based on the results of the initial test of students' mathematical communication skills, it is known that 3 indicators of mathematical communication skills have not been able to be achieved by students. This study aims to determine and describe mathematical communication skills using the Teams Games Tournament cooperative learning model in terms of the initial ability is better than conventional learning of class IX students of SMP N 28 Sarolangun. This study uses a quantitative approach with an experimental method with a 2 x 3 factorial design. Based on the results of the data analysis for the experimental class and the control class it can be concluded that: Hypothesis (1) Mathematical Communication Ability Using Cooperative Learning Model Teams Game Tournanent in terms of Initial Capability is better than Learning Conventional. Hypothesis (2) Mathematical Communication Ability Using Cooperative Learning Model Teans Gams Tournament in terms of High Initial Ability is no better than conventional learning. Hypothesis (3) Mathematical Communication Ability Using Teams Games Tournament Cooperative Learning Model in terms of Initial Medium Ability is better than conventional learning. Hypothesis (4) Mathematical Communication Ability Using Teams Games Tournament Cooperative Learning Model in terms of Low Initial Ability is no better than conventional learning. Hypothesis (5) There is an interaction between the Teams Game Tournament learning model and conventional learning in terms of initial ability to influence mathematical communication skills.